Blue-Violet Organic Electroluminescent Devices Based on Exciton-Confined Structure - 张积梅 蒋雪茵 张志林 朱文清 吴有智 郑新友 姜标 付克洪 (Journal of Shanghai University, 2005)
Three types of blue-violet light-emitting devices based on an exciton-confined structure have been prepared, in which different materials were used as emitting layers and hole-transporting layers. They had structures of ITO/CuPc/NPB/CPB/TPBi/Alq3/LiF/Al(DNC), ITO/CuPc/JO3/CBP/TPBi/Alq3/LiF/Al(DJC ) and ITO/CuPc/JO3/FNPD/TPBi/Alq3/LiF/Al(DJF). Here copper phthalocyanine (CuPc) acted as hole-injecting layer( HIL), N, N-bis-(1-naphthyl)-N, N-diphenyl-1. lbiphenyl-4-4-diamine(NPB) and J03 bole-transporting layers ( HTLs), 4,4'-dicarbazolyl-1,1' -biphenyl (CBP) and FNPD as emitting layers( EMLs), N, arylbenzimidazoles (TPBi) as holeblocking layer ( HBL ), and tris(8-quinolinolato ) aluminium complex ( Alq3 ) as electron- transporting layer ( ETL). TPBi applied here is a good confinement to both charges and excitons, which make the devices emit blue-violet light originating from the emitter, CBP and FNPD. Their characteristics have also been investigated. The result shows that the device DNC based on NPB/CBP has the best performance among the three devices. The excellence of DNC is attributed to the better hole-transporting ability of NPB as compared with J03, and the better emitting ability of CBP as compared with FNPD, although the best matching of energy levels is found in the hole-transporting layer and emitting layer of the device DJP.